2021
DOI: 10.1039/d0ra08679g
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotube materials for electrocardiography

Abstract: Carbon nanotubes as 1D nanomaterials of excellent physicochemical characteristics bring hope to compete and eventually conquer traditional solutions in electrocardiography – the most powerful non-invasive diagnostic tools in cardiac disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 145 publications
(104 reference statements)
0
15
0
Order By: Relevance
“…Perhaps the most explored area of research in the analyzed field deals with the use of CNTs for electrocardiography [ 146 ]. As recently demonstrated by Kolanowska and colleagues, CNTs excel in this field due to their high flexibility, impressive electrical conductivity, and low mass density, which dramatically reduces the device’s weight [ 147 ].…”
Section: The Opportunities Offered By Wearable Sensors From Cntsmentioning
confidence: 99%
“…Perhaps the most explored area of research in the analyzed field deals with the use of CNTs for electrocardiography [ 146 ]. As recently demonstrated by Kolanowska and colleagues, CNTs excel in this field due to their high flexibility, impressive electrical conductivity, and low mass density, which dramatically reduces the device’s weight [ 147 ].…”
Section: The Opportunities Offered By Wearable Sensors From Cntsmentioning
confidence: 99%
“…[27][28][29] Therefore, various studies have been conducted on transparent and flexible functional electrodes composed of CNT-based soft polymers. [30][31][32] Specifically, it is possible to establish a scalable solution-based process by controlling the CNT content of the non-porous network in the soft polymer and the strength of the interface between the polymer and CNTs functionalized with various functional groups. Gilshteyn et al reported a singlewalled CNT (SWCNT)/hydrogel-based electrode with a transmittance of 60% and an elasticity range of 15%-100% by transferring an SWCNT film, synthesized via an aerosol (floating catalyst) chemical vapor deposition method, to the hydrogel structure.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite these notable efforts, the development of scalable and cost-effective ECG wearable electrodes via controlled interfacial engineering between soft polymers and carbon nanomaterials such as SWCNTs, MWCNTs, and graphene remains a challenge. 31,[37][38][39] In this study, a wearable electrode based on PDMS-1D SWCNTs/2D reduced graphene oxide (r-GO) with uniform and excellent conductivity was developed. In addition, an ECG system with Bluetooth features, which facilitates accurate and continuous wireless monitoring, was explored by introducing a customized electrode with a macro grid pattern structure exhibiting low skin-electrode contact resistance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome the biocompatibility effects, recent advances in electrode materials have been made, in order to achieve comfortable, flexible and biocompatible electrodes. A wide variety of materials have been employed, such as carbon nanomaterials [1], carbon nanotubes [2], metallic nanoparticles [3], inorganic semiconductors [4], and electroconductive polymers. Conductive polymers are very promising for electrode materials because they are soft, electrically conductive, low cost, easily synthesized, and biocompatible with human tissues [5] [6].…”
Section: Introductionmentioning
confidence: 99%